The utility of CT scan for identifying hollow viscus injury in blunt abdominal trauma: a systematic review - Gul Muhammad, Marium; Winston, David; Pina, Nancy; Kasprzycki, Tomasz; McCutcheon, Brion; Joyner, Robert; Kowdley, Gopal C. (International Surgery Journal, 2025)
Introduction: Computed tomography (CT) is the preferred imaging modality for assessing blunt abdominal trauma and is the gold standard for detecting hollow viscus injuries. CT may occasionally miss significant injuries in such settings. This systematic review examines the incidence of hollow viscus injury in blunt abdominal trauma and evaluates the diagnostic accuracy of the initial trauma CT. Method: A keyword search for PubMed, SCOPUS, Web of Science and Embase was undertaken. Key words “hollow viscus injury” and “blunt abdominal trauma” were used. Inclusion criteria included blunt abdominal trauma, adult population and English language. This search identified 1826 studies. After abstract screening and full text review, 15 studies met criteria to be included in this review. Result: All studies were retrospective in design and were from trauma centers. A total of 20199 patients had CT scans upon admissions following blunt trauma. The incidence of hollow viscus injury was found to be 14.45% (n=2920/20199). Location of injuries included stomach 0.079% (n= 16/20199), duodenum 0.41% (n=84/20199), Ileum/jejunum 1.65% (n=333/20199), large intestine 0.81% (n=164/20199) and unspecified bowel injuries 11.5% (n=3049/20199). There were a total of 217/20199 (1.07%) injuries that were missed on the initial CT scan. Patients with hollow viscus injury, but negative initial CT scans, were identified within 36 hours of presentation. Conclusion: Although CT scan is a very effective and widely used method for identification of hollow viscus injury in blunt trauma, it is not always definitive. Patients with hollow viscus injury that were missed on initial CT scans were identified within 36 hours of presentation.